2017
DOI: 10.1103/physrevb.96.075408
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-resolved second harmonic generation microscopy of chiral G-shaped metamaterials

Abstract: Chiral planar metamaterials are known for their possibility to show strong nonlinear optical effects such as second harmonic generation (SHG) circular dichroism or asymmetric SHG. The underlying mechanisms are commonly discussed in terms of local field effects and formation of localized SHG sources (so called "hotspots") that are sensitive to the shape and size of meta-atoms. Nevertheless, a full characterization of the polarization state of the nonlinear optical radiation from the hotspots has not been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…[28] Subsequently,t he research on SHG-CD mainly focused on biological tissues (collagen), [29] nanoparticle dimers, [30] plasmonic metasurfaces, [31] metamaterials. [32,33] In addition, as we known that, growing high quality single crystal with large size for the study of nonlinear optics is crucial necessary,w hich can be achieved available length in the phase matching direction. [34] Nevertheless, through comprehensive research, we find that the SHG-CD effect in chiral OIHPs bulk single crystals is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Subsequently,t he research on SHG-CD mainly focused on biological tissues (collagen), [29] nanoparticle dimers, [30] plasmonic metasurfaces, [31] metamaterials. [32,33] In addition, as we known that, growing high quality single crystal with large size for the study of nonlinear optics is crucial necessary,w hich can be achieved available length in the phase matching direction. [34] Nevertheless, through comprehensive research, we find that the SHG-CD effect in chiral OIHPs bulk single crystals is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas SHG-CD has been demonstrated from numerous chiral nano/metamaterials, far less attention has been devoted to SHG-OR. Previous studies have demonstrated SHG-OR in plasmonic nanostructures, where the origin of the effect can be ambiguous. Indeed, SHG-OR can be due to both intrinsic structural chirality and sample anisotropy.…”
mentioning
confidence: 99%
“…[ 20 , 21 ] Therefore various optical metasurfaces have been proposed for enhancing SHG, and the intensity, phase, and polarization states of the induced SHG can be precisely manipulated by optimizing the sizes, shapes, and orientations of the metallic nanostructures. [ 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Therefore various optical metasurfaces have been proposed for enhancing SHG, and the intensity, phase, and polarization states of the induced SHG can be precisely manipulated by optimizing the sizes, shapes, and orientations of the metallic nanostructures. [10,[22][23][24][25][26][27][28][29][30] The traditional optical buck metamaterial can generate second harmonic nonlinearity with efficient conversion by using phase matching techniques. The optical metasurfaces have exhibited novel nonlinear properties that were not found in the natural nonlinear buck optical crystals, and they provide a promising venue for enhancing and manipulate SHGs.…”
Section: Introductionmentioning
confidence: 99%